Genome Sequence of Cotton Leafroll Dwarf Virus Infecting Cotton in Georgia, USA - Tabassum, Afsha (Microbiol Resour Announc, 2020)
Cotton leafroll dwarf disease (CLRDD), caused by the aphid-borne Cotton leafroll dwarf virus (CLRDV; genus, Polerovirus; family, Luteoviridae), has been recently reported from the major cotton-growing regions of the United States. Here, we present the nearly complete genome sequence of a CLRDV isolate from cotton in Georgia.